Seroprevalence of SARS-CoV-2 infection in a municipality in southern Brazil (Research, Society and Development, 2021)
SARS-CoV-2 is an RNA virus, responsible for causing an acute respiratory syndrome, which became known worldwide for its rapid spread and for causing the pandemic of a new disease: COVID-19. Thus, epidemiological studies have been developed in order to determine the extent of the problems and the magnitude of the disease. The present study aimed to evaluate the seroprevalence of SARS-CoV-2 infection and its relationship with socio-demographic and clinical-epidemiological factors in the city of Chapecó, Santa Catarina, Brazil. It was a quantitative, epidemiological, observational, cross-sectional, population-based study with 2179 participants. Socio-demographic, associated behavioral, aggravating and comorbid parameters were evaluated, relating them to positivity or not in the rapid test implemented. The rapid test identified 22.2% of the diagnosed seroprevalence of COVID-19 in the municipality in question. A higher incidence of cases was observed in people living with other people, in people who had contact with positive cases, and in symptomatic patients, corroborating with current studies. The results highlight the importance of clinical-epidemiological studies for the understanding and control of COVID-19.